LEXICAL DRIFT, METAPHOR AND LACUNA: AN ANALYSIS OF PROVERBS IN THE WORK “DEVONU LUGAT-IT TURK” FROM THE PERSPECTIVE OF TRANSLATION STUDIES (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the proverbs in the work «Devonu lugat-it turk” by Mahmud Kashgari. The main focus of the research is on the problems of lexical drift (meaning shift), metaphorical shifts and cultural lacunas (gaps) in translation studies. The semantic changes and cultural differences that occur in the process of translating ancient Turkic proverbs in the work into modern Uzbek and English are revealed from a scientific perspective.
Keywords: “Devonu lugat-it turk”, Mahmud Kashgari, lexical drift, metaphor, lacuna, translation studies, proverbs, ethnolinguistics, equivalence.